An acoustic study on monophthongs in Central Australian Aboriginal English - Wang, Yizhou; O'Shannessy, Carmel; Davis, Vanessa; Bundgaard‐Nielsen, Rikke; Foster, Denise (World Englishes, 2025)
We present an acoustic analysis of monophthongal vowel production in Central Australian Aboriginal English (CAAE), providing one of the first systematic examinations of this variety spoken by English‐as‐a‐first‐language (L1) speakers in Mparntwe/Alice Springs, Australia. Using conversational data from six adult female participants, we investigated the acoustic properties of CAAE's vowel system, focusing on phonemic contrasts, phonetic realisations, allophonic variations and individual differences. The analyses reveal that CAAE has a similar vowel inventory to Mainstream Australian English (MAusE), but also displays some distinct phonetic features. For instance, in CAAE, the trap vowel is less open than that in MAusE, and some CAAE speakers may produce the goose vowel as a back vowel. Like other varieties, phonological contexts affect vowel production, as allophonic variations have also been observed. Together, the analyses contribute to a more detailed understanding of the phonetics and phonology of CAAE spoken as an L1 in Central Australia today.